Cardiopulmonary Exercise Testing Using the Modified Balke Protocol in Fully Ambulatory People With Multiple Sclerosis. Issue 2 (April 2021) - Feasel, Corey D.; Sandroff, Brian M.; Motl, Robert W.
Abstract : Purpose: This study examined the application, outcomes, and validity of cardiopulmonary exercise test (CPET) outcomes using a modified Balke protocol on a motor-driven treadmill in fully ambulatory people with multiple sclerosis (MS). Methods: Fully ambulatory people with MS (N = 20) underwent assessments of disability (Expanded Disability Status Scale, EDSS), walking endurance (6-minute walk distance, 6MWD), and cognition (Symbol Digit Modalities Test, SDMT), and completed a maximal CPET (modified Balke protocol) on a motor-driven treadmill while expired gases were collected with indirect calorimetry. Serious adverse events (AEs) and AEs, defined by National Institutes of Health guidelines, and provision of a "maximal" effort test using standard criteria for a maximal effort were documented. The physiological outcomes derived from the CPET included oxygen uptake (V[Combining Dot Above]O2 ), carbon dioxide production, ventilation (VE), respiratory exchange ratio, and heart rate (HR). Other outcomes were calculated using standard guidelines, including V[Combining Dot Above]O2 /HR slope and oxygen uptake efficiency slope (V[Combining Dot Above]O2 /log10VE). Descriptive statistics were summarized with mean ± SD and descriptively compared with normative data from apparently healthy individuals using a similar CPET protocol. Spearman's rho rank-order correlations (ρ) were performed among peak V[Combining Dot Above]O2 and SDMT, 6MWD, and EDSS scores. Results: There were no AEs, and 17 of 20 tests were characterized as yielding a maximal effort and therefore interpretable. V[Combining Dot Above]O2 peak derived from the modified Balke protocol was predictably different in MS (25.8 ± 6.3) than normative values for healthy samples men (43.4 ± 9.3) and women (35.0 ± 7.2). V[Combining Dot Above]O2 peak positively correlated with SDMT ( ρ = 0.53, P = .01) and 6MWD (ρ = 0.73, P = .0003), and negatively correlated with disability (ρ = −0.51, P = .02). Conclusions: Cardiopulmonary exercise test using a modified Balke protocol on a motorized treadmill is safe, feasible, and valid for the measurement of aerobic power in fully ambulatory people with MS.